1997
DOI: 10.1007/s002280050241
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of intravenously administered mibefradil, a new calcium antagonist, on the electrophysiologic characteristics of the human heart

Abstract: At plasma levels close to those found after chronic oral administration of 50 and 100 mg mibefradil, the higher dose produced an increase in corrected sinus node recovery time. Mibefradil also produced small but significant effects on AV nodal conduction and increased AV nodal refractoriness. Mibefradil had no effect on any other electrophysiologic parameter and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…While mibefradil shares with verapamil and diltiazem the ability to lower HR, it is the only CA that decreases HR without concomitantly suppressing cardiac contractility at therapeutic concentrations [26,27]. Indeed, the lack of negative inotropic effect and the absence of reflex tachycardia and neurohormonal activation [6] coupled with the anti-anginal and anti-ischemic efficacy of mibefradil suggest that the compound may have a role in the treatment of patients with left-ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…While mibefradil shares with verapamil and diltiazem the ability to lower HR, it is the only CA that decreases HR without concomitantly suppressing cardiac contractility at therapeutic concentrations [26,27]. Indeed, the lack of negative inotropic effect and the absence of reflex tachycardia and neurohormonal activation [6] coupled with the anti-anginal and anti-ischemic efficacy of mibefradil suggest that the compound may have a role in the treatment of patients with left-ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…81 At the clinical level, mibefradil was not associated with QT prolongation but was associated with bradycardia and an increase in sinus node recovery time. 87,88 Another anti‐anginal agent associated with QT prolongation, perhexiline, has been shown to inhibit heterologously expressed HERG channels. 89 The block by perhexiline is use and voltage dependent and a hyperpolarizing shift in the voltage dependence of steady state inactivation suggests that the agent may bind to the inactivated state of the channel.…”
Section: Acquired Lqts and Pharmacological Inhibition Of Ikrmentioning
confidence: 99%
“…The same decrease was observed in earlier studies with 100 mg once-daily mibefradil given long-term to healthy volunteers. Mibefradil appears to decrease heart rate by a direct effect on the SA node, as shown in a study with isolated dog sino-atrial preparations (23) and also suggested by invasive electrophysiological measurements in humans (24). An additive effect of digoxin and mibefradil in decreasing heart rate was seen, indicating that both drugs have a direct effect on the SA node.…”
Section: Discussionmentioning
confidence: 84%